VectorCollection_SIVIZ_project_Portugal - Hugo Osório (GBIF Sweden, 2025)
Dataset containing the records of vectors collected under the REVIVE program to the SIVIZ project in Portugal
Keywords: Occurrence; Observation; OCCURRENCE; Biological Sciences; Biologi